Bramwell. The complete second season [videorecording (DVD)] - Redgrave, Jemma; Calder, David, 1946-; McMonagle, Kevin; Sheen, Ruth; Connolly, Andrew (Shanachie Entertainment, 2007)
Television series that follows the fortunes of public health heroine Dr. Eleanor Bramwell as she takes on the medical establishment in Victorian-era London. In the second season, Eleanor finds her private practice failing and faces tough choices ahead in her encounters with a case of spousal abuse, pre-teen prostitution, an outbreak of cholera, and a mysterious aunt with a secret to hide. Along the way, she falls in love with her handsome and charismatic new partner at work, Dr. Finn O'Neill.